Water Security in the Syr Darya Basin - Kai Wegerich; Daniel Van Rooijen; Ilkhom Soliev; Nozilakhon Mukhamedova (Water, 2015)
The importance of water security has gained prominence on the international water agenda, but the focus seems to be directed towards water demand. An essential element of water security is the functioning of public organizations responsible for water supply through direct and indirect security approaches. Despite this, there has been a tendency to overlook the water security strategies of these organizations as well as constraints on their operation. This paper discusses the critical role of water supply in achieving sustainable water security and presents two case studies from Central Asia on the management of water supply for irrigated agriculture. The analysis concludes that existing water supply bureaucracies need to be revitalized to effectively address key challenges in water security.
Keywords: 330; water security; supply water security; irrigation bureaucracy; polycentric water management; transboundary; Central Asia